Manual de gestión de la tecnología en la clínica Universidad de la Sabana, teniendo como referencia la resolución 3100 de 2019 (2020)
Clinical Engineering (CI) is a field of action of biomedical engineering focused on health technology and hospital management. It seeks to provide safety and quality in patient care while maintaining an adequate cost / benefit ratio, through procedures focused on medical devices and equipment. In 2019, the Ministry of Health issued a new resolution for the authorization of health services, which generated changes in the authorization requirements and a need to update the management processes. To carry out this update, a technology management manual was developed based on Resolution 3100 of 2019, which "defines the procedures and conditions for the registration of health service providers and the authorization of health services."